Did the Cholera epidemic in Haiti really start in the Artibonite Department? - Rafael Llanes; Lorenzo Somarriba; Placido Pedroso; Emiliano Mariscal; Carlos Fuster; Yamila Zayas (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.